Asymptomatic lung abscess of aspergillus in a female without previous lung diseases or immunocompromise: a case report - Hanxue Xiang; Ling Zhang; Liu Yang; Miaotian Cai; Yingmin Ma; Yulin Zhang (BMC Infectious Diseases)
Abstract Background Chronic pulmonary abscess usually results from bacterial or mycobacterium infection, but rarely from aspergillosis. Chronic pulmonary aspergillosis is usually found in a person with structural lung disease or immunocompromise. Here, we report a case of chronic lung abscess of aspergillosis without immunocompromise, structural lung diseases or even clinical symptoms. Case presentation A 43-year-old female was found a mass shadow with central liquid anechoic area in the apical posterior segment of the left upper lung lobe by chest computerized tomography for 1 month, but had no any systematic or respiratory complaints. The percutaneous abscess puncture was performed and 30 milliliters of yellow purulent fluid were aspirated from the liquid anechoic area. Then Aspergillus terreus was detected by both fluid culture and metagenomics next-generation sequencing. Interestingly, this patient had no history of tuberculosis or chronic pulmonary diseases. Other immunocompromised conditions were also denied through history inquest and laboratory tests. Ultimately, the catheterization and drainage of the lung abscess and 6 months of antifungal therapy with standard dose of voriconazole brought the woman a favorable outcome. Conclusion Aspergillus lung abscess can occasionally occur in a person without pre-existent lung cavity and immune suppression, which is prone to misdiagnosis because of the rarity and the symptom-free.